Numerical modeling of magnetic field impact on the thermal behavior of a microchannel heat sink - Bahram Jalili; Amirhossein Rezaeian; Payam Jalili; Fathollah Ommi; Davood Domiri Ganji (Case Studies in Thermal Engineering, 2023)
The current appraisal evaluates the heat transfer phenomena of the nanofluid stream through the microchannel heat sink, considering the existence of a magnetic field. Moreover, Aluminum oxide (Al2o3)-water nanofluid is elected and implemented as a cooling fluid in this study. Also, the Koo–Kleinstreuer model (KKL correlation) is provided for the computation of the viscosity and effectual thermal conductivity of the nanofluid. Improved Darcy relationship is used for modeling the porous medium, and the two-equation approach's dispersion type is utilized for poking the heat transfer phenomenon among the solid and fluid zones. Due to the nonlinearity of the linked heat transfer relationships in mentioned phases, the well-known analytical Collocation method (CM) model decodes the issue. The influence of the void fraction and the diameter of the nanoparticles, temperature distribution, Hartmann number, fluid velocity, and channel geometry are discussed comprehensively. The obtained outcomes indicate that implementing the magnetic field has a direct connection with the Nusselt number. It was also found that heat transfer increases with the increase in nanofluid concentration. So, for the concentration of 0.04, there is the highest amount of heat transfer.